Komparasi tingkat efisiensi antara bank Syariah milik pemerintah dan privat serta pengaruh struktur kepemilikan terhadapnya - Imam Haroki Enayatullah (Journal of Enterprise and Development (JED), 2020)
Numerous studies indicate that government control of a bank has a detrimental effect on its performance. Is this usually the case and does it apply to all types of banks? This is the research question. This paper examines eight Islamic commercial banks in Indonesia as a case study. The study spans the years 2013–2017. The analysis is conducted in two parts. The first stage involves determining the efficiency of the system using the Stochastic Frontier Analysis (SFA) Panel method. Efficiency testing is conducted using two approaches: the intermediation approach and the asset approach. The second objective is to analyze the effect of ownership on efficiency using a panel technique. Testing for efficiency using both the asset and intermediation approaches reveals that the government-owned BUS operates at the maximum level of efficiency. The average value of government BUS efficiency is likewise greater than the average for non-government BUS. Examinations of the effect of ownership reveal that there is no substantial relationship between ownership and efficiency.